2022
DOI: 10.3390/ijerph192215253
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Firefighters’ Physical Ability Test Scores from Anaerobic Fitness Parameters & Mental Toughness Levels

Abstract: Physical ability test (PAT) evaluates firefighters’ (FF) occupational capacity. The contribution of anaerobic systems during PAT and mental toughness (MT) relationship to PAT is unexplored. PAT modeling based on anaerobic fitness (AF), MT, and respective relationships were examined. Fourteen male FFs (Age: 29.0 ± 7.0 years) completed a PAT composed of occupationally-specific tasks in full gear. On a separate day, a series of AF assessments were performed (handgrip-dynamometry: HG; vertical-jump: VJ; Margaria-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…This research was structured as a longitudinal study conducted in two waves, situated within an ongoing series of studies investigating the relationship between physiological and psychological attributes in relation to the Physical Ability Test (PAT) (for more details on the followed methodology, please see [6]). This longitudinal approach enabled a comparative analysis of MT at different time points while avoiding the common design in MT research (i.e., cross-sectional), thereby enriching the understanding of MT's role in firefighters' performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research was structured as a longitudinal study conducted in two waves, situated within an ongoing series of studies investigating the relationship between physiological and psychological attributes in relation to the Physical Ability Test (PAT) (for more details on the followed methodology, please see [6]). This longitudinal approach enabled a comparative analysis of MT at different time points while avoiding the common design in MT research (i.e., cross-sectional), thereby enriching the understanding of MT's role in firefighters' performance.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the apparent importance of MT in the inherently stressful context of firefighting, there is a conspicuous absence of dedicated instruments designed to measure this construct within this specific setting [6]. Recently, Beitia et al [6] employed the peer-rated Military Training Mental Toughness Inventory (MTMTI) [7] and the self-rated Sports Mental Toughness Questionnaire (SMTQ) [8] to assess MT within a firefighter cohort for two primary reasons: (a) the extant literature on MT is predominantly characterized by crosssectional self-assessment methodological designs [9] and (b) the traumatic experiences encountered in military settings bear tactical similarities to those in firefighting [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the average duration of FSAs, 20–45 min repeated 2–4 times per event, and short rest interval (5–10 min), there is a reliance on both aerobic and anaerobic (glycolytic) sources of energy [ 15 ]. In a 2022 study, Beitia and colleagues [ 16 ] reported that 35–60% of metabolic demands during structured firefighting activities come from anaerobic energy production due to the extended time working at 97% of their VO 2 max. A study by von Heimberg et al [ 17 ] noted that, due to the limited volume of air contained within SCBA (self-contained breathing apparatus) devices, firefighters who can complete tasks faster would conceivably consume less air, indicating a need for a developed anaerobic capacity, such as time worked.…”
Section: Introductionmentioning
confidence: 99%